Spatial engineering of single-atom Fe adjacent to Cu-assisted nanozymes for biomimetic O2 activation - Wang, Ying; Paidi, Vinod K.; Wang, Weizhen; Wang, Yong; Jia, Guangri; Yan, Tingyu; Cui, Xiaoqiang; Cai, Songhua; Zhao, Jingxiang; Lee, Kug-Seung; Lee, Lawrence Yoon Suk; Wong, Kwok-Yin (Nature communications, 2024)
The precise design of single-atom nanozymes (SAzymes) and understanding of their biocatalytic mechanisms hold great promise for developing ideal bio-enzyme substitutes. While considerable efforts have been directed towards mimicking partial bio-inspired structures, the integration of heterogeneous SAzymes configurations and homogeneous enzyme-like mechanism remains an enormous challenge. Here, we show a spatial engineering strategy to fabricate dual-sites SAzymes with atomic Fe active center and adjacent Cu sites. Compared to planar Fe–Cu dual-atomic sites, vertically stacked Fe–Cu geometry in FePc@2D-Cu–N–C possesses highly optimized scaffolds, favorable substrate affinity, and fast electron transfer. These characteristics of FePc@2D-Cu–N–C SAzyme induces biomimetic O 2 activation through homogenous enzymatic pathway, resembling functional and mechanistic similarity to natural cytochrome c oxidase. Furthermore, it presents an appealing alternative of cytochrome P450 3A4 for drug metabolism and drug–drug interaction. These findings are expected to deepen the fundamental understanding of atomic-level design in next-generation bio-inspired nanozymes. Integrating heterogeneous single atom nanozyme (SAzyme) configurations and homogeneous enzyme-like mechanism is promising for optimizing SAzymes but elusive. Here the authors address this issue by developing a spatial engineering strategy to fabricate dual-sites SAzymes incorporating single atom Fe active centers (Fe–N 4 ) and Cu atomic sites (Cu–N 4 ) in a vertically stacked Fe–N 4 and Cu–N 4 geometry.